A study on isothermal oxidation kinetics using thermogravimetric method of TiNiNb shape memory alloys - Balci, E.; Somunkiran, I.; Ercan, E.; Dagdelen, F.; Aydogdu, Y. (Springer, 2023)
In this study, thermal oxidation behavior of Ti50Ni29Nb21, Ti50Ni28Nb22, Ti50Ni27Nb23, and Ti50Ni26Nb24 (atomic %) shape memory alloys was investigated thanks to thermogravimetric analysis. These alloys were exposed to oxygen atmosphere isothermally, i.e., between 700 and 900 C, for 1 h. After this process, the surface oxidation is found to involve the formation of a few distinctive product layers. The oxide regions formed and grew with increasing temperature. It was revealed that the oxidation response of containing equal-Ti alloys is very sensitive to the niobium content and the oxidation temperatures. Moreover, it was determined that the surface oxidation behavior of the alloys saturates at high temperatures. The oxide layers formed in the SEM-EDX analyzes of the Nb21 Alloy were observed and the rutile TiO2 and NiTiO3 phases were determined. The results will provide valuable insights into the behavior of TiNiNb SMAs during isothermal oxidation and will help to improve our understanding of these materials and their potential applications. The findings of this study could have significant implications for the design and use of TiNiNb SMAs in a wide range of applications, including medical devices, aerospace, and automotive industries.
Keywords: Isothermal oxidation; Kinetics; TiNiNb shape memory alloys; Phase transformation; Structural properties